Teacher Emotional Intelligence: Analysis Based on Work Commitment, Spiritual Intelligence, and Pedagogical Competence of Arabic Language Teachers in Bengkalis Regency - Putra, Muhammad Wira Dana; Hermita, Neni; Isjoni, Isjoni (CV. Tripe Konsultan, 2024)
Emotional intelligence greatly affects individual teachers such as Arabic language teachers, it can be seen that emotions act as an impetus from within the teacher as a step to act and Arabic language teachers who are identical with high emotionality can affect students. This study aims to determine the influence of variables (1) work commitment on emotional intelligence, (2) spiritual intelligence on emotional intelligence (3) pedagogic competence on emotional intelligence, (4) work commitment to spiritual intelligence, (5) work commitment to pedagogic competence (6) spiritual intelligence to pedagogic competence, (7) work commitment, intelligence and pedagogic competence on emotional intelligence. Respondents of this study were Arabic language teachers who taught at MI / SD, MTs / SMP, and MA / SMA Negeri and Private in Bengkalis Regency. The population was 125 people with a sample of 96 Arabic language teachers. Data analysis using path analysis. The research findings show that work commitment has an indirect impact on emotional intelligence (0.368), spiritual intelligence has an indirect impact on emotional intelligence (0.549), pedagogical competence has a direct impact on emotional intelligence (0.714), and work commitment has a direct impact on spiritual intelligence (0.628), 628), there is a direct influence between work commitment on pedagogical competence, the magnitude of the direct influence between work commitment on pedagogical competence is 0.383, there is a direct influence between spiritual intelligence on pedagogical competence, the magnitude of the direct influence between spiritual intelligence on pedagogical competence is 0.492. Thus it can be concluded that there is a direct and indirect influence between work commitment, spiritual intelligence and pedagogical competence on the emotional intelligence of Arabic language teachers in Bengkalis Regency.